Humidity control by using bamboo charcoal as dehumidifier - Malek, Nur Shazuanee; Barkeshli, Mandana (2012)
Controlling humidity in museum environment will help to expand object’s life. It is because humidity is one of the agents of deterioration. Incorrect humidity will lead microorganism to grow, and artifact became porous. In this study bamboo charcoal as dehumidifier has been introduced to control humidity. It is a desiccant to remove moisture from air by blowing it through a drying or desiccant material such as silica gel. Unfortunately, silica gel will affect human by occurring skin irritation if it is handled in improper way. Silica gel more over It is from synthetically sodium silicate and chemical based. However, bamboo charcoal is a new approach to replace a silica gel as dehumidifier. It is a green product coming from nature, environment friendly and easier to get. Furthermore, it has a porous structure and high porosity absorption to control humidity and to purify the air.